2017
DOI: 10.1021/acs.jpcc.7b04045
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur-Capped Germanium Nanocrystals: Facile Inorganic Ligand Exchange

Abstract: The development of applications for germanium nanocrystals has been hindered by the limited availability of synthetic methods coupled with poorly understood ligand-exchange chemistry. Herein we describe the synthesis of germanium nanocrystals and ligand exchange experiments designed to establish facile routes toward ligand replacement and, consequently, layers that are amenable to charge-transfer. After assessing thiols, carboxylates, and dithiocarbamates, sulfur dissolved in 1-ocatadecene was determined to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…12 Beginning with the work of Boyle et al in 2005, 13 synthesizing colloidal Ge nanocrystals by the high-temperature chemical reduction of Ge(II) and/or Ge(IV) precursors in long-chain aliphatic primary amines has become common practice, 12,[14][15][16] resulting in nanocrystals passivated by surface-coordinated amine ligands. While only a few ligand exchange reactions on these Ge nanocrystals have been reported thus far, it has been demonstrated that the native primary amine ligands can be at least partially exchanged with thiols, 12,17 polyethyleneimine, 11 and polysulfides 18 via room temperature exchange reactions. When colloidal Ge nanocrystals are synthesized by the chemical reduction of GeI 2 in oleylamine by microwave heating, instead of conventional heating, the resulting nanocrystals are similarly supported by surface oleylamine ligands; 19,20 however, it was reported that these native oleylamine ligands can only be efficiently exchanged with thiols after surface reduction with hydrazine followed by heating the nanocrystals in neat thiol.…”
Section: Introductionmentioning
confidence: 99%
“…12 Beginning with the work of Boyle et al in 2005, 13 synthesizing colloidal Ge nanocrystals by the high-temperature chemical reduction of Ge(II) and/or Ge(IV) precursors in long-chain aliphatic primary amines has become common practice, 12,[14][15][16] resulting in nanocrystals passivated by surface-coordinated amine ligands. While only a few ligand exchange reactions on these Ge nanocrystals have been reported thus far, it has been demonstrated that the native primary amine ligands can be at least partially exchanged with thiols, 12,17 polyethyleneimine, 11 and polysulfides 18 via room temperature exchange reactions. When colloidal Ge nanocrystals are synthesized by the chemical reduction of GeI 2 in oleylamine by microwave heating, instead of conventional heating, the resulting nanocrystals are similarly supported by surface oleylamine ligands; 19,20 however, it was reported that these native oleylamine ligands can only be efficiently exchanged with thiols after surface reduction with hydrazine followed by heating the nanocrystals in neat thiol.…”
Section: Introductionmentioning
confidence: 99%
“…A −10.0 V bias was applied to the sample to further enhance collection of the lowest kinetic energy electrons during UPS experiments. 28 Charging (or lack thereof) was verified by acquiring C 1s spectra with and without the charge neutralizer to determine if any shifts in the core level peaks were noticeable. Devices were fabricated and tested via previously established protocols and tested in accordance to standard testing procedures.…”
mentioning
confidence: 99%
“…Characterization was carried out in a Kratos Axis-Ultra using an Al Kα source (1486.6 eV) and He­(I) excitation source (21.2 eV) for XPS and UPS, respectively. A −10.0 V bias was applied to the sample to further enhance collection of the lowest kinetic energy electrons during UPS experiments . Charging (or lack thereof) was verified by acquiring C 1s spectra with and without the charge neutralizer to determine if any shifts in the core level peaks were noticeable.…”
mentioning
confidence: 99%
“…27 The surface chemistry can greatly affect certain chemical and physical properties, making the type of ligand at the surface extremely important. 28,29 For example, although organic ligands offer excellent chemical flexibility as capping groups, 30 they are highly insulating, making them nonideal for electronic devices. 27 Removal of organic ligands through annealing, however, can lead to sintering and cracks in films.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Surface ligands play a critical role in the colloidal stability and ordered self-assembly of NCs . The surface chemistry can greatly affect certain chemical and physical properties, making the type of ligand at the surface extremely important. , For example, although organic ligands offer excellent chemical flexibility as capping groups, they are highly insulating, making them nonideal for electronic devices . Removal of organic ligands through annealing, however, can lead to sintering and cracks in films. ,− Replacing the insulating, organic ligands with conducting, inorganic ligands that offer optimum colloidal stability in solution via a ligand exchange would help mitigate these issues as well as improve charge carrier mobility in thin film assemblies (Scheme ).…”
Section: Introductionmentioning
confidence: 99%